Synthesis of C-Glucosyl Aminooxy Esters - Peyrat, Sandrine; Cheng, Keguang; Xie, Juan (Synthesis, 2013)
Glycosyl amino acids are constituents of glycopeptides and glycoproteins playing key roles in biological processes. We have synthesized C-glucosyl aminooxy acid derivatives as novel glycosyl amino acid building blocks for the generation of glycopeptide and glycoprotein mimics. These compounds can be readily prepared from C-allyl glucosides, through dihydroxylation, selective tritylation, Mitsunobu reaction with PhthNOH, detritylation, and oxidation. Both C-glucosyl l- and d-α-aminooxy esters have been successfully synthesized. With the ready availability of C-allyl glycosides, the present methodology could be applied to the synthesis of other C-glycosyl aminooxy acid derivatives.
Keywords: aminooxy acids; glycopeptides; glycosyl aminooxy acids; C-allyl glycosides; Mitsunobu reaction